Disentangling the developmental origins of a novel phenotype: enhancement versus reversal of environmentally induced gene expression. Issue 1985 (26th October 2022) - Levis, Nicholas A.; McKay, Daniel J.; Pfennig, David W.
Abstract : Increasing evidence suggests that many novel traits might have originated via plasticity-led evolution (PLE). Yet, little is known of the developmental processes that underpin PLE, especially in its early stages. One such process is 'phenotypic accommodation', which occurs when, in response to a change in the environment, an organism experiences adjustments across variable parts of its phenotype that improve its fitness. Here, we asked if environmentally induced changes in gene expression are enhanced or reversed during phenotypic accommodation of a novel, complex phenotype in spadefoot toad tadpoles ( Spea multiplicata ). More genes than expected were affected by both the environment and phenotypic accommodation in the liver and brain. However, although phenotypic accommodation primarily reversed environmentally induced changes in gene expression in liver tissue, it enhanced these changes in brain tissue. Thus, depending on the tissue, phenotypic accommodation may either minimize functional disruption via reversal of gene expression patterns or promote novelty via enhancement of existing expression patterns. Our study thereby provides insights into the developmental origins of a novel phenotype and the incipient stages of PLE.